Influence of chain length and branching on poly(ADP-ribose)–protein interactions. Issue 2 (10th January 2023) - Löffler, Tobias; Krüger, Annika; Zirak, Peyman; Winterhalder, Martin J; Müller, Anna-Lena; Fischbach, Arthur; Mangerich, Aswin; Zumbusch, Andreas
Abstract: Hundreds of proteins interact with poly(ADP-ribose) (PAR) via multiple PAR interaction motifs, thereby regulating their physico-chemical properties, sub-cellular localizations, enzymatic activities, or protein stability. Here, we present a targeted approach based on fluorescence correlation spectroscopy (FCS) to characterize potential structure-specific interactions of PAR molecules of defined chain length and branching with three prime PAR-binding proteins, the tumor suppressor protein p53, histone H1, and the histone chaperone APLF. Our study reveals complex and structure-specific PAR–protein interactions. Quantitative K d values were determined and binding affinities for all three proteins were shown to be in the nanomolar range. We report PAR chain length dependent binding of p53 and H1, yet chain length independent binding of APLF. For all three PAR binders, we found a preference for linear over hyperbranched PAR. Importantly, protein- and PAR-structure-specific binding modes were revealed. Thus, while the H1-PAR interaction occurred largely on a bi-molecular 1:1 basis, p53—and potentially also APLF—can form complex multivalent PAR–protein structures. In conclusion, our study gives detailed and quantitative insight into PAR–protein interactions in a solution-based setting at near physiological buffer conditions. The results support the notion of protein and PAR-structure-specific binding modes that have evolved to fit the purpose of the respective biochemical functions and biological contexts.